Making conversation in modernist fiction - Alsop, Elizabeth (Theory and interpretation of narrative series., 2019)
"Analyzes the function of dialogue in early twentieth-century novels and discusses works by Henry James, James Joyce, Ernest Hemingway, William Faulkner, Virginia Woolf, and Gertrude Stein"--